Influence of the sintering temperature on ferroelectric properties of potassium-sodium niobate piezoelectric ceramics - Cortés, J. A. [UNESP]; Camargo, J.; Rachia, M. F. [UNESP]; Rubio-Marcos, F.; Ramajo, L.; Castro, M.; Ramírez, M. A. [UNESP] (World Scientific Publishing, 2021)
The effect of sintering condition on structure, microstructure, and ferroelectric properties of (K0.44Na0.52Li0.04) (Nb0.86Ta0.10Sb0.04)- O3 (KNL-NTS) has been investigated. Ceramic powders have been synthesized by the solid-state reaction method and sintered at different temperatures (1115°C, 1125°C, and 1140°C). Then, samples were characterized by thermogravimetric analysis, X-ray diffraction, scanning electron microscopy, and impedance spectroscopy. Through XRD results, the perovskite structure and small peaks corresponding to a secondary phase were detected. Ceramics processed at the highest temperatures showed higher densities and good piezoelectric properties (d33, Kp, and Kt), particularly specimens sintered at 1125°C presented the highest piezoelectric performance.
Keywords: ferroelectric properties; KNL-NTS; lead-free